Plays and performance texts by women, 1880-1930 : an anthology of plays by British and American women from the modernist period - Gale, Maggie B, Ed (Women, theatre and performance, 2012)
"This groundbreaking anthology, part of the Women, Theatre and Performance series, brings together an extraordinary mix of one-act and full length plays and solo performance texts written by women. Included in the volume are texts by Beatrice Herford, Ruth Draper, Zora Neale Hurston and G.B. Stern, originally performed across commercial and amateur theatres in Britain and America. Some of the plays have remained unpublished since their original performance -- Georgina Weldon's Not Alone, Clothilde Graves' Mother of Three, Rachel Crother's Ourselves and Marie Stope's Our Ostriches. Others are anthologized here alongside plays with which they connect aesthetically and historically, for example, Edith Lyttelton's Warp and Woof, Elizabeth Robins' Votes for Women, Elizabeth Baker's Edith, Sophie Treadwell's Machinal and Aimée Stuarts' Nine Till Six. The volume, for students and scholars, provides an accessible collection of texts exemplifying the range and breadth of women's theatre writing from the 1880s to the early decades of the twentieth century."--Publisher's website.